Aerosol optical properties observed by combined Raman‐elastic backscatter lidar in winter 2009 in Pearl River Delta, south China. Issue 5 (7th March 2014) - Chen, Zhenyi; Liu, Wenqing; Heese, Birgit; Althausen, Dietrich; Baars, Holger; Cheng, Tianhai; Shu, Xiaowen; Zhang, Tianshu
Abstract We present combined Raman and elastic backscatter lidar observations in Zhongshan, PRD (Pearl River Delta), China, during two periods in 2009: one haze period and one moderate pollution period. During the haze period, high Aerosol Optical Depth (AOD) (0.86 and 1.20 at 355 nm) and medium Ångström exponents (1.23 and 1.35 at 355 nm/532 nm) were observed. In the moderate pollution period, the corresponding parameters were comparatively lower with values of 0.83 and 0.74 at 355 nm for AOD and 1.108 and 0.98 at 355 nm/532 nm for Ångström exponent. The mean lidar ratios in the two periods were 64 ± 10 sr and 56 ± 9 sr, respectively, at 355 nm. The Ångström exponent was calculated for the extinction from the wavelength pair 355 nm/532 nm, with high values of around 1.35 for the haze event. The particle size distribution and single‐scattering albedo derived from Sun photometer measurements indicate the presence of rather small particles. The 3 day back trajectories from a Hybrid Single‐Particle Lagrangian Integrated Trajectory model in the haze period indicate that the air masses in the lower layer were advected from the southeast coast of China, where incomplete combustion of carbonaceous fuels and straw burning are frequently found in Shanghai during the heating period in winter. In the moderate pollution period, the air mass passed through western China, indicating a combination of some pollution from South Asia in case of strong convection, local aerosol aging, and smoke from adjacent fire burning spots in the PRD region.